Intrinsic and Extrinsic Motivation to E learning in Higher Education Institutions - Al-Alwani, Abdulkareem (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
There were many researches which were conducted about implementation of e learning in Higher Education Institutions, but few of them were focused on the motivation of e learning. Even though, there are many applications of e learning in Higher Education Institutions, it is very obvious that there is a resistance to e learning from many users in different fields. The researcher in this study tries to examine the knowledge of selected faculty members to know what their motivations are towards e learning. The research explores various intrinsic and extrinsic motivations such as physical resources, accessibility to internet, perception towards e learning, training, pedagogy and teaching strategies, confidence, comparison to face-to-face teachings, time factor, administrative support, lack of time for students, lack of monitoring, recognition, workload, relevancy to taught courses, in-adequate release time, age, and students technical knowledge. Faculty from various countries responded ‘strongly agree that adequate and workable physical resources, and accessibility to internet have high percentage (>30%) that motivates them to utilize e learning. While a small percentage chose less agree and disagree to other responses that contribute to motivation towards e learning.